Effect of environmental change on yield and quality of fruits and vegetables: two systematic reviews and projections of possible health effects - Pauline F D Scheelbeek, PhD; Hanna L Tuomisto, PhD; Frances A Bird, MSc; Andy Haines, FMedSci; Alan D Dangour, PhD (Elsevier, 2017)
Background: Environmental changes-including climatic change, land degradation, water scarcity, and biodiversity loss-threaten agricultural production and quality and pose challenges to global food security. Most research in this area has focused on staple crop yields. By contrast, relatively little attention has been given to fruits and vegetables that are important for nutrition and health, including for the prevention of non-communicable diseases. In this study, we review the evidence of the effects of environmental change on the yield and quality of fruits and vegetables, and assess possible implications for nutrition and health outcomes. Methods: We undertook two systematic reviews of the global published literature on the effect of environmental change on (1) yields and (2) nutritional quality of fruits and vegetables. We evaluated the evidence for 12 different environmental stressors: here we focus on atmospheric temperature and CO2 concentrations, and precipitation patterns. Data were analysed from two study types: greenhouse experiments and model simulations. We used the review findings to assess the possible health consequences of changed availability and quality of fruits and vegetables in low-income, middle-income, and high-income settings. Findings: Although findings varied between crop type and climatic zones, we did identify some consistent trends. In tropical countries, there were largely adverse effect on yield of increased temperature and changing precipitation patterns, although in more temperate zones some beneficial effects on yield were reported. Increased CO2 concentration had a predominantly positive effect on yield. The effects of (moderate) increases in temperature and reduced precipitation on nutritional quality of fruits and vegetables were mostly positive with higher vitamin, mineral and soluble solid contents measured in many crops, largely as a result of plant stress responses. Increased atmospheric CO2 concentrations had predominantly negative effects on nutritional quality of fruits and vegetables. Because most studies investigated one change, the combined and interactive effects of all environmental stressors remain unclear. Adverse health implications, including the potential for nutrient deficiencies and related chronic diseases were estimated to be largest in areas characterised by high vulnerability to environmental change and high rates of poverty and food insecurity, as well as areas that are highly dependent on local markets. Interpretation: Our reviews identified effects of environmental change on yields and quality of fruits and vegetables that might pose threats to population health, especially in areas vulnerable to climate-change and food insecurity: directly through reduced consumption, and indirectly through income pathways that might result in restricted household dietary energy intake and dietary diversity. To obtain more precise estimates of the change in burden of disease and mortality attributable to affected yields and quality of fruits and vegetables, further research is needed on farmers' and consumers' adaptation and substitution strategies. Furthermore, the combined effect of multiple environmental stressors on fruit and vegetable yield and quality should be further quantified. These data would allow development of future scenarios, based on projected environmental changes and simulations of human behaviour change. Funding: Wellcome Trust.